2017
DOI: 10.3171/2016.2.jns152855
|View full text |Cite
|
Sign up to set email alerts
|

Functional approach using intraoperative brain mapping and neurophysiological monitoring for the surgical treatment of brain metastases in the central region

Abstract: OBJECTIVE Brain metastases are the most frequent intracranial malignant tumor in adults. Surgical intervention for metastases in eloquent areas remains controversial and challenging. Even when metastases are not infiltrating intra-parenchymal tumors, eloquent areas can be affected. Therefore, this study aimed to describe the role of a functional guided approach for the resection of brain metastases in the central region. METHODS Thirty-three patients (19 men and 14 women) with perirolandic metastases who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 47 publications
2
17
0
2
Order By: Relevance
“…В функциональной нейрохирургии двига-тельных нарушений (например, при болезни Паркинсона) применяют микроэлектродную регистрацию суммарной активности подкор-ковых структур для последующей установки электродов нейромодулятора. Классическими примерами способов локализации структур-но-функциональных образований, с помощью которых оценивают сохранность определенной функции, стали методики интраоперационно-го картирования моторной коры и речевых зон [2,6,[11][12][13][14].…”
Section: Discussionunclassified
“…В функциональной нейрохирургии двига-тельных нарушений (например, при болезни Паркинсона) применяют микроэлектродную регистрацию суммарной активности подкор-ковых структур для последующей установки электродов нейромодулятора. Классическими примерами способов локализации структур-но-функциональных образований, с помощью которых оценивают сохранность определенной функции, стали методики интраоперационно-го картирования моторной коры и речевых зон [2,6,[11][12][13][14].…”
Section: Discussionunclassified
“…[1][2][3]21,37 Several studies showed that decreasing mapping MEP thresholds correlates with the risk of mechanical injury to the CST. 5,6,34,[38][39][40] Applying monopolar subcortical cathodal short train stimulation at low stimulation intensities, we demonstrated that mapping motor thresholds correlate with the risk of CST injury.…”
Section: Continuous Subcortical Mappingmentioning
confidence: 99%
“…The surgical resection of brain metastases located in eloquent areas remains a particular challenge due to the higher risk of postoperative neurological and neurocognitive de cits [5,21]. It is a crucial issue since survival is linked to both the extent of resection and the functional status of the patient [21].…”
Section: Introductionmentioning
confidence: 99%
“…3) better control of the surgical risks regarding metastases initially deemed inoperable and previously treated with stereotactic radiotherapy for which a histomolecular diagnosis is required. Previous series have reported awake surgery for brain metastases [7,9,10,21]. Two pioneer studies from Dusseldorf reported that awake surgery is feasible for metastases in eloquent areas, minimizing postoperative neurologic de cits and morbidity and permitting supramarginal resection [9,10].…”
Section: Introductionmentioning
confidence: 99%